Culture as a Factor of Continuity in the Development of Society - Ziyatbay, Abjamiev (Indonesian Journal Publisher, 2024)
This article examines the role of culture as a pivotal factor in the continuity and development of society. It explores the dynamics of spiritual culture, highlighting the interconnectedness of historical stages and the processes of inheritance that shape cultural evolution. The discussion draws on insights from prominent philosophers such as Hegel, Plekhanov, and others, emphasizing the dialectical nature of cultural inheritance and the complex relationships between past and present. The article delves into various cultural phenomena, including the Baroque period, folklore, and mythological traditions, illustrating how these elements contribute to the ongoing dialogue between historical legacy and contemporary identity. By analyzing the mechanisms of cultural assimilation and the transformation of ideas over time, the article underscores the significance of understanding cultural heritage as a continuous, evolving process that informs present and future societal values.